2019
DOI: 10.1101/748251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variation in parental effects contribute to the evolutionary potential of prey responses to predation risk

Abstract: 23Despite the ubiquity of parental effects and their potential impact on evolutionary dynamics, 24 their contribution to the evolution of ecologically relevant adaptations remains poorly 25 understood. Using quantitative genetics, here we demonstrate that parental effects contribute 26 substantially to the evolutionary potential of larval antipredator responses in a leaf beetle 27 (Leptinotarsa decemlineata). Previous research showed that larger L. decemlineata larvae elicit 28 stronger antipredator responses,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This finding is consistent with our earlier line-cross study of larval size (Zakas and Rockman 2014), which found statistical evidence for more-thanmaternal genetics, including negative effects of lecithotrophic paternity on larval size, at least in some maternal backgrounds. Paternal genetic effects in species without parental care are rare but not unprecedented (Crean and Bonduriansky 2014;Tigreros et al 2019). The biology of Streblospio benedicti permits several possible mechanisms of paternal effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with our earlier line-cross study of larval size (Zakas and Rockman 2014), which found statistical evidence for more-thanmaternal genetics, including negative effects of lecithotrophic paternity on larval size, at least in some maternal backgrounds. Paternal genetic effects in species without parental care are rare but not unprecedented (Crean and Bonduriansky 2014;Tigreros et al 2019). The biology of Streblospio benedicti permits several possible mechanisms of paternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Paternal genetic effects in species without parental care are rare but not unprecedented (Crean and Bonduriansky 2014 ; Tigreros et al. 2019 ). The biology of Streblospio benedicti permits several possible mechanisms of paternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our earlier line-cross study of larval size (Zakas and Rockman 2014), which found statistical evidence for more-than-maternal genetics, including negative effects of lecithotrophic paternity on larval size, at least in some maternal backgrounds. Paternal genetic effects in species without parental care are rare but not unprecedented (Crean and Bonduriansky 2014;Tigreros et al 2019). The biology of Streblospio benedicti permits several possible mechanisms of paternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of genetic variation accumulating in populations that display transgenerational plasticity. For instance, additive genetic variation underlies transgenerational plasticity in antipredator responses of the leaf beetle ( Leptinotarsa decemlineata ; Tigreros et al, 2019). Regardless of whether this genetic accumulation results from the exposure of cryptic genetic variants or from the decoupling of genotypes and phenotypes across generations (as discussed above), such accumulation of genetic variation may allow for canalization of the adaptive plastic responses.…”
Section: Plastic Rescue As An Initial Step Toward Evolutionary Rescuementioning
confidence: 99%